The effect of counseling self-control program on the psychological endurance of the hookah players blind players under (20 years) (Journal of the College of Basic Education, 2023)
The field of psychology has witnessed a great development, especially with regard to creating psychological situations in a way that provokes the player's motives and access to sports achievement. As self-control represents the main part in preparing the player to acquire skills, attitudes, goals and all dimensions of competition from stadiums, referees, devices and tools, and psychological endurance plays a major role in preparing players and increasing their ability to face psychological pressures and the ability to achieve their goals. As for the research problem, the lack of attention to the psychological aspect, in addition to the lack of special psychological programs for the players of the blind gun, in addition to the lack of the use of the self-control program. The aim of the research was to prepare a program for self-control and to know the extent of its effect on psychological endurance and some offensive skills of the blind weapon The experimental approach with two groups, the experimental and the control, was used. The sample size was (20) of Diyala club players with the hook weapon and psychological endurance was measured. A set of conclusions has been reached, the most important of which are: - There are significant differences in the psychological stress scale of the sample under study between the members of the experimental and control groups and in favor of the experimental group. There are significant differences in the psychological stress scale of the sample under study between the two posttests of the experimental and control groups, in favor of the post test. The most important recommendations are the necessity of using the self-control program prepared by the researcher in developing the psychological endurance of the blind players for the category of applicants. And the need to pay attention to the psychological aspect of the players.